2020
DOI: 10.3390/foods9091172
|View full text |Cite
|
Sign up to set email alerts
|

Is a Consumer Perception of Salt Modification a Sensory or a Behavioural Phenomenon? Insights from a Bread Study

Abstract: Salt plays a major role in food manufacturing and affects the technological and sensory properties of foods. At the same time, high dietary salt intake increases the risk of cardiovascular diseases and represents a considerable public health concern. In many populations, bread is a major contributor to salt intake and is therefore targeted by health policies recommending salt reduction reformulations. However, producers are often reluctant to reduce salt content due to fears of potential negative effects on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 91 publications
1
15
1
Order By: Relevance
“…This suggests that, overall, consumers like a lower level of sodium in their multigrain bread as much as a multigrain bread without sodium reduction. Prior research has found 15% reducedsodium multigrain bread without additional reduction strategies to be liked significantly less than the nonreduced counterpart; in contrast, results from this study suggest incorporating MSG may mitigate palatability loss of reduced-sodium breads when added salt is limited in the recipe's formulation (Kuhar et al, 2020). Saltiness liking does not differ from the full sodium sample when up to 43% of sodium is reduced regardless of whether MSG is included, indicating saltiness liking is negatively impacted in multigrain breads only when a greater portion of sodium is reduced from the formulation.…”
Section: Consumer Acceptance For Breads With Different Levels Of Sodi...contrasting
confidence: 81%
“…This suggests that, overall, consumers like a lower level of sodium in their multigrain bread as much as a multigrain bread without sodium reduction. Prior research has found 15% reducedsodium multigrain bread without additional reduction strategies to be liked significantly less than the nonreduced counterpart; in contrast, results from this study suggest incorporating MSG may mitigate palatability loss of reduced-sodium breads when added salt is limited in the recipe's formulation (Kuhar et al, 2020). Saltiness liking does not differ from the full sodium sample when up to 43% of sodium is reduced regardless of whether MSG is included, indicating saltiness liking is negatively impacted in multigrain breads only when a greater portion of sodium is reduced from the formulation.…”
Section: Consumer Acceptance For Breads With Different Levels Of Sodi...contrasting
confidence: 81%
“…The intention of purchase of green shoots was correlated with the overall impression (Spearman correlation = .483, n = 35, p < .01) but none of these attributes was significantly correlated with saltiness. This may indicate that the public awareness on the relation between dietary salt and cardiovascular disease makes saltiness a less valued attribute (Kuhar, Korošec, Bolha, Pravst, & Hristov, 2020;Lopes, Cavaleiro, & Ramos, 2017). Other characteristics, like colour, succulence and crispness, and the presence of solutes associated with the UMAMI taste (Guerreiro et al, 2018) may significantly contribute to the overall pleasant perception of S. ramosissima shoots in mixed salads and the intention of purchase.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, the authors concluded that the salt-reduced breads were well-accepted by children. Kuhar et al (2020) assessed how salt content influences consumer' liking and saltiness perception in white and multigrain breads. Treatments evaluated include a control with salt content based on Slovenia's national average in bread, a reduced treatment with International Journal of Food Science and Technology 2021 15% less salt than the control and an increased treatment with 10% greater salt than the control.…”
Section: Reduction Of Saltmentioning
confidence: 99%